UTILIZATION OF MADE AQUIFERS TO IMPROVE THE QUALITY OF CLEAN WATER TO DRINKING WATER - Mohammad Imamuddin; Acep Hidayat (University Of Muhammadiyah Jakarta, 2021)
The need for clean water quality has increased every year, especially in big cities in Indonesia. This is triggered by the high population growth which causes the need for clean water to be urgently needed. Lack of water catchment areas and green land exacerbates the amount of clean water. In addition, the cause of the decline in clean water quality is also influenced by the many negative activities carried out by humans, one of which is the activity of disposing of garbage in the river, reservoir / setu and drainage areas. The use of chemicals, namely Poly Aluminum Cholrid (PACPOWDER) in the processing of river water or river water requires high operational costs, which results in high costs for people who subscribe to PDAM. The filtering pattern of water can be done by referring to the soil layer in the form of an aquifer, so that the water that is not good can be filtered in the presence of an aquifer and can purify the water into drinking water. The use of artificial aquifers that have currently been carried out by the Ministry of Public Works is through rain, where through the filtration of rainwater containing acidic levels it can be neutralized through artificial aquifers into clean water and can be applied to areas of high drought levels.